Census Exercise - Roy, William (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The exercise is to code two pages from the manuscript pages of the U.S. Census of 1880 for Los Angeles. The manuscript is found on microfilm in Microfilm Reading room at URL under the Call Number: HA 201 1880, A25, Reels 66,67. U.S. Census. Tenth Census. 1880. Select any two pages to code. Photocopy the pages there. It is also available on Ancestry.com, but you have to register for a free trial period; www.familysearch.org, also has it, but I couldn’t figure out how to use except to search for particular names. What sense do you make of what you find here? You can do simple statistical analysis (with Excel, STATA, or any other software you have your disposal) or do a more informal analysis. If you do an informal analysis, tell how you would make it rigorous if you were doing it for real? Do you see anything that supports or challenges Laslett’s findings about LA 1850-70? You can find PDF files of the published census reports, which would have complete aggregate results for Los Angeles or California at http://www.census.gov/prod/www/abs/decennial/1880.htm. If you compare the results from your arbitrarily selected sample with the full population results, you will quickly learn the importance of sampling. Write a maximum of five double spaced pages.